Investigative Study of Partial Replacement of Cement with Bio-Cement, Fly Ash and Natural Pozzolans (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Concrete is usually a combination of cement, coarse particles (aggregates and Sand) and water. It is used to design and improve the infrastructures.It is used to design and improve the infrastructures. Concrete has many advantages and disadvantage. The main property that is characteristic to a concrete’s workability is its compressive strength. Only through this single test, one can judge if cementing has been done appropriately. Possible advancements for development include the use of non-traditional and creative materials, and the reuse of waste materials with a specific end goal to replenish the absence of specific assets and to discover alternative ways to monitor the Earth..This investigation concentrate on Compressive strength, flexural and split tensile strength of Conventional Concrete (CC) and Class C fly ash remains with bio-cement and natural pozzolans to consider the impact of bio-concrete with blend extents of 0%,0.25%,0.5%,1% and 1.5% on quality properties. Moreover, effective self-healing usually occurred due to the use of polymers, microorganism and additional cementing material. It is the key issue to find out the self-healing efficiency’s effect to sealing the crack width successfully. And good resistance was observed during the bacterial chemical process against the freeze and thaw attacks.